Elephant impacts on woody vegetation around artificial waterholes in Zambezi National Park, Zimbabwe - Wilson, Luke (Department of Biological Sciences, 2020)
Elephant are renowned for their ability to substantially alter vegetation. However, as they need to drink regularly, surface water exerts a strong influence over the distribution and magnitude of elephant impacts on vegetation. This study was conducted in Zambezi National Park, a 560 km2 unfenced protected area in northwest Zimbabwe. It aimed to investigate the impacts of elephant on woody vegetation, particularly in relation to artificial waterholes. Sampling plots were located at different distances from four pumped waterholes in teak (Baikiaea) and Terminalia woodlands, the two main woody vegetation types recognised in the study area. Plots were set at 200, 500, 1000, 2000 and 4000 m from waterholes in the teak woodland. Due to the close proximity of waterholes, a lower maximum distance of 2500 or 3000 m from waterholes had to be used in the Terminalia woodland, but sampling intervals from 200-2000 m were otherwise the same. Assessment of elephant browsing and a series of measurements were performed on trees and shrubs within these plots, with plants assigned to one of three height classes (0.2 - < 1 m; 1 - <3 m and ≥3 m). Elephant dung counts were also conducted in these plots, to provide a measure of elephant occupancy. A clear decline in elephant browsing with distance from waterholes was evident in both the teak and Terminalia woodlands. However, elephant browsing was consistently higher in the latter woodland type. Averaged across all plant height classes, elephant had removed 30-45% of plant canopies in most Terminalia woodland plots. More moderate canopy removal of 10- 30% was found in most teak woodland plots. Plants ≥3 m were particularly highly browsed in the Terminalia woodland, with over 50% of their canopy volume removed in most plots. Elephant browsing impacts were also considered at the species level, which revealed clear differences in browsing levels among species. Some uncommon and highly browsed species were flagged as being potentially vulnerable to disappearance from the area, even in the teak woodland where overall elephant browsing was lower. The effects of elephant browsing on vegetation structure at different distances from artificial waterholes were also investigated. Little change was apparent in the teak woodland, where the only noted impact was a reduction in the density and canopy volume of plants 1 - <3 m tall, limited to within 1 km of waterholes. More pronounced structural impacts were evident in the Terminalia woodland. Substantial declines in the basal area and canopy volume of trees (i.e. plants ≥3 m) occurred closer to waterholes, with widespread conversion of woodland to shrubland evident. Reductions in both tree and shrub canopy volumes closer to waterholes also suggested a reduction in browse availability in the Terminalia woodland. Finally, elephant dung declined with distance to waterholes, confirming that elephant were found in higher densities closer to waterholes. However, dung counts did not reveal different levels of elephant occupancy between the two vegetation types, despite higher browsing in the Terminalia woodland. This finding suggests elephant might be using the teak woodland for purposes other than just browsing, such as for shade. The study thus provided evidence that waterholes have had a significant impact on vegetation in the area, particularly on the favoured Terminalia woodland. Acknowledging the tourism value of retaining waterholes in the area, it is suggested that distances between waterholes should be increased, through only continuing pumping at waterholes with viewing platforms. This could result in a more heterogeneous elephant browsing regime across the highly impacted Terminalia woodland in particular, and lessen further homogenisation of this vegetation type towards a shrubland.